Assessing emotion regulation repertoires: The Regulation of Emotion Systems Survey. (1st December 2017) - De France, Kalee; Hollenstein, Tom
Abstract: Research has shown a link between emotion regulation (ER) repertoire, the range of ER strategies an individual employs and the degree to which they rely on them, and well-being. However, this advancement is hindered by the lack of a single measurement tool capable of assessing multiple ER strategies on a common scale. The current paper reports on two studies utilizing the Regulation of Emotion Systems Survey (RESS), a new self-report measure allowing for variable- and person-centered analyses of six common ER strategies (Distraction, Rumination, Reappraisal, Suppression, Engagement, Arousal Control). Study 1 (n = 1582) included scale development, validation, and Latent Profile Analysis (LPA). Results showed the RESS is a valid, reliable, and effective measure. Three profiles were identified (Average, Suppression Propensity, Engagement Propensity). The Average group reported greater psychosocial functioning than the Suppression group. Study 2 (n = 100) LPA indicated 4 profiles (Average, Suppression Propensity, Engagement Propensity, Multi-strategy) and assessed the effects of emotionality. The Average group reported lower emotional awareness than the Engagement and Multi-Strategy groups. Profiles did not differ on frequency or intensity of emotions. Findings demonstrated the utility of the RESS and confirm the importance of ER repertoires to better understand connections between ER and well-being. Highlights: The RESS is a valid, effective, and reliable measure of six common ER strategies. ER profiles with average levels of all ER strategies demonstrated greater wellbeing. Intensity and frequency of emotional experiences did not influence ER repertoire.